2017
DOI: 10.3389/fnins.2017.00660
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stockwell Transform to Electroencephalographic Signal Analysis during Gait Cycle

Abstract: The analysis of electroencephalographic signals in frequency is usually not performed by transforms that can extract the instantaneous characteristics of the signal. However, the non-steady state nature of these low voltage electrical signals makes them suitable for this kind of analysis. In this paper a novel tool based on Stockwell transform is tested, and compared with techniques such as Hilbert-Huang transform and Fast Fourier Transform, for several healthy individuals and patients that suffer from lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Another study reported in [23] achieved an accuracy of 72.91% with 71.81±11.48% true positive rate and 4.56 ±1.84 FP/ min for start detection and accuracy, TPR and FP/min of 80.65±11.49%, 57.38 ±12.03% and 2.10 ±1.20 for stop detection. In a more recent study [52], the accuracy, sensitivity and FP/min were reported as 78.61±11.20%, 76.90±11.75% and 3.52±1.82 for start detection and 84.36±10.19%, 68.68±14.69% and 2.06±1.12 for stop detection. It is to be noted though that these studies used a very large detection window of 4s containing data from two seconds before the starting and stopping event to two seconds after the occurrence of the event.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Another study reported in [23] achieved an accuracy of 72.91% with 71.81±11.48% true positive rate and 4.56 ±1.84 FP/ min for start detection and accuracy, TPR and FP/min of 80.65±11.49%, 57.38 ±12.03% and 2.10 ±1.20 for stop detection. In a more recent study [52], the accuracy, sensitivity and FP/min were reported as 78.61±11.20%, 76.90±11.75% and 3.52±1.82 for start detection and 84.36±10.19%, 68.68±14.69% and 2.06±1.12 for stop detection. It is to be noted though that these studies used a very large detection window of 4s containing data from two seconds before the starting and stopping event to two seconds after the occurrence of the event.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the recent technologies have shown promise to make possible innovations in experimental designs for a lot of BCI systems. In addition to that, traditional spatial filtering techniques including Laplacian filtering and common average referencing are also available as alternative [22,23,52]. These filters aim to minimize the contribution of the rest of the EEG electrodes to each channel thus better isolating the information from each of the electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al contrario que en otras investigaciones previas realizadas [12,13], donde las señales se utilizan para generar un modelo independiente por sujeto de pruebas, esta investigación requiere de una comparación de los parámetros extraídos entre sujetos. Por ello, es necesario llevar a cabo una normalización que nos permita comparar en una misma escala los datos extraídos.…”
Section: Normalización De Las Señales Eegunclassified
“…In these paradigms, the extraction of features is usually accomplished by the filtering of the frequency bands, associated with the rhythms related to the brain activity being analyzed. Although the features are generally extracted using traditional signal processing filters, there are other alternatives in the literature based on time vs. frequency analysis techniques, such as the wavelet transform (Xu and Song, 2008 ; Yang et al, 2010 ; Kant et al, 2019 ) and the Stockwell transform (Ortiz et al, 2017 ). However, they have not been used in conjunction with an exoskeleton (He et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%